DAMPELAS ORAL LITERATURE LEGACY BY LITERATURE STRATEGY ON LITERATURE REVITALIZATION ACTIVITIES - M. Asri B.; Tamrin Tamrin; Nursyamsi Nursyamsi; Sitti Harisah (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
The results of the study stated that the Dampelas oral literature needs to be revitalized because it was only a matter of counting the fingers of the speakers who could use it and it was rarely displayed in traditional events. This oral literature also needed to be inherited because it contains many virtues and was very beneficial for the younger generation as the next generation. The target of this oral literature revitalization activity was a community of 100 junior high school (junior high) children, which was divided into 90 junior high school students and 10 accompanying teachers. There were three resource persons/maestros who passed on Dampelas oral literature through literacy strategies, namely reading, chanting or singing verses that had been prepared by the resource person (maestro). The types of Dampelas oral literature that were revitalized were (1) modade oral literature, namely the type of oral literature in the form of Dampelas language poetry, (2) mobabai oral literature, which was a type of Dampelas language folk song.